2004
DOI: 10.1002/chem.200305661
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Human Tropoelastin: Solution Structure, Dynamics and Self‐Assembly of the Exon 5 Peptide

Abstract: The elastic properties of elastin have essentially been discussed in terms of dominant entropic components, with questions still remaining about whether the basic mechanism is compatible with the classical theory of rubber elasticity. A better understanding of the structure-function relationships in terms of the protein's elastic properties remains an important goal in elastin science. Recently, we succeeded in the exon-by-exon synthesis of all polypeptide sequences encoded by the so-called hydrophobic exons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…Basically, one could do careful measuring of Noe volumes of sequential and intraresidue Ha-HN NOE crosspeaks. 3,34 This volume ratio analysis requires reduced overlap of the signals, difficult to find for glycine-rich elastomeric peptides. On the other hand, the method put forward by Lam and Hsu 55 is interesting; however it requires further validation before becoming a standard protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, one could do careful measuring of Noe volumes of sequential and intraresidue Ha-HN NOE crosspeaks. 3,34 This volume ratio analysis requires reduced overlap of the signals, difficult to find for glycine-rich elastomeric peptides. On the other hand, the method put forward by Lam and Hsu 55 is interesting; however it requires further validation before becoming a standard protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the individual exons encoding an independent and selfcontained structure has been called the ''reductionist approach'' and has been shown to work in a series of papers. [14][15][16][30][31][32][33][34] Obviously, this approach will not apply to globular proteins where the concept of autonomous domains is usually not applicable. However, even in the case of elastin some scepticism could be present.…”
Section: Elastinmentioning
confidence: 98%
“…The choice of these solvents has been rationalized in previous papers. 4,5 Boc-MG-OH. 1 N NaOH (160 ml) was added to a solution of 0.160 mol of Boc-MG-OEt in acetone (36 ml).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In the latter case, CD (and NMR) spectroscopy allowed the proposal of a new molecular model of elasticity based on dynamic equilibria between extended (PPII, b-strands) and folded (b-turn) conformations. 4,5 Within the framework of this research area, we decided to apply the same approach to abductin, the protein responsible for compressive elasticity for the abductor ligament in bivalves. 6 The known conceptual amino acid sequence of abductin derived from Argopecten irradians 7 revealed the presence of three prominent amino acids: glycine, methionine, and phenylalanine ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the ability of the elastin precursor molecule to undergo self-aggregation is an important property of the assembly process, the steps involved in elastic fiber formation are not precisely known (5). Actually, it has been widely demonstrated that even short peptides and simple polymeric sequences belonging to elastin are able to give filaments with twisted-rope, hierarchical supramolecular organization similar to that found for the entire protein (6,7). Interestingly, Miao et al (8) have found that some mutated polypeptide sequences encoded by exons of human tropoelastin exhibit an ultrastructural organization different from the fibrils typical of elastin but rather similar to those found for amyloid networks, constituted by helical fibrils several microns long and about 10 nm wide (9).…”
mentioning
confidence: 99%